Preparation method of low-alkali thermally activated muck-cement-based mixed geopolymer concrete and prefabricated steel reinforced column

Through the preparation method of low alkaline heat activated slag-cement-based mixed land polymer concrete, the problems of resource waste and environmental pollution in the traditional concrete production process are solved, and the effective utilization of slag and improvement of concrete performance are achieved.

CN119774924APending Publication Date: 2025-04-08SHEN ZHEN SHI JIN ZHONG JI TUAN GU FEN YOU XIAN GONG SI +4
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411696025.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the traditional concrete production process, there are problems such as high energy consumption, serious environmental pollution and shortage of natural resources, and the engineering waste cannot be effectively utilized, resulting in waste of resources and environmental pollution.

Method used

The preparation method of low alkaline heat activated slag-cement-based mixed land polymer concrete is adopted. Through drying, screening, thermal activation and mixing, slag is used to replace part of the cement, reducing dependence on natural aggregates, and optimizing the concrete performance through water glass and feed.

Benefits of technology

It realizes effective utilization of slag, reduces energy consumption and environmental pollution, improves the strength and durability of concrete, and is in line with the development trend of green and environmentally friendly building materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and particularly relates to a preparation method of low-alkali thermally activated muck-cement-based mixed geopolymer concrete and a prefabricated steel reinforced column. Comprising the following steps that S1, soil is taken from project earthwork excavation to serve as raw material muck, and the taken muck is dried through drying equipment; s2, screening the muck in the step S1, dividing the muck into muck powder and gravel particles, mixing the muck powder with sodium hydroxide, activating through heat treatment calcination, mixing with cement, stirring to form a heat activated muck-cement-based mixture, and separating the gravel particles to obtain coarse and fine aggregates; s3, mixing the thermally activated muck-cement-based mixture and water glass to form neat paste; and S4, stirring the neat paste, water, coarse and fine aggregates and an additive to form concrete. Application of the muck-cement-based geopolymer concrete prefabricated steel reinforced column can be effectively achieved, assembly type construction of a composite structure can be achieved in cooperation with the prefabricated beam-column joint, and recycling of solid waste materials is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a preparation method of low-alkali heat-activated slag-cement-based mixed geopolymer concrete and a prefabricated steel column. Background Art

[0002] With the rapid development of urbanization and the shortage of land resources, the stock of construction waste has increased dramatically, accounting for nearly 60% of the total construction and demolition waste. Most of the construction waste is transported to landfills, and a large amount of construction waste is piled up and cannot be used, which requires high transportation costs and leads to urban traffic congestion, environmental pollution, and safety hazards. Traditional concrete uses cement as a hydraulic cementitious material mixed with sand and gravel to form, but because cement production requires a "two grinding and one burning" process, it consumes a lot of energy. With the rapid development of urban construction, more and more buildings need to use natural aggregates to produce lightweight concrete. Due to the shortage of natural resources, its cost remains high.

[0003] Based on the concept of geopolymer concrete, appropriate slag is used to replace cement while ensuring that there is no significant change in material strength, so as to achieve the gradual consumption of construction slag. Therefore, how to use slag in geopolymer concrete and how to produce low-cost, high-strength, good working performance and green concrete are of great significance to the development of the current building materials industry. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings involved in the above concrete preparation process and provide a method for preparing low-alkali heat-activated slag-cement-based mixed geopolymer concrete.

[0005] The present invention adopts the following technical solutions: A method for preparing low-alkali heat-activated slag-cement-based mixed geopolymer concrete comprises the following steps: S1. Take soil from the project excavation as raw material slag, and dry the taken slag through drying equipment; S2, the slag in step S1 is screened and divided into slag powder and crushed stone particles, the slag powder is mixed with sodium hydroxide, activated by heat treatment and calcination, and then mixed with cement to form a heat-activated slag-cement-based mixture, and the crushed stone particles are separated to obtain coarse and fine aggregates; S3, mixing the heat-activated slag-cement-based mixture and water glass to form a slurry; S4. Mix the pure paste with water, coarse and fine aggregates and external materials to form concrete.

[0006] Specifically, the excavated soil from the project is used as raw material, which effectively utilizes the soil that might have been discarded. This not only reduces the land resources occupied by soil landfill, but also reduces the transportation costs, traffic congestion and environmental pollution caused by soil landfill.

[0007] Specifically, during the preparation process, crushed stone particles are obtained by screening the slag, and coarse and fine aggregates are further separated, reducing the dependence on natural aggregates. The use of recycled aggregates can alleviate the shortage of natural aggregate resources and realize the recycling of resources. The slag powder is subjected to thermal activation treatment, and then mixed with sodium hydroxide and calcined by heat treatment, which can change the physical and chemical properties of the slag and improve the activity of the slag, so that after it is mixed with cement to form a thermally activated slag-cement-based mixture, it can better exert its gelling properties, help enhance the strength and stability of concrete, enable concrete to withstand greater loads in building structures, and improve the safety and durability of buildings.

[0008] Specifically, the heat-activated slag-cement-based mixture is mixed with water glass to form a paste, which is then mixed with water, coarse and fine aggregates, and additives to form concrete. This mixing method allows various materials to work synergistically with each other. Water glass can further improve the adhesion of the paste, while the combination of the paste and coarse and fine aggregates can make the internal structure of the concrete denser, and the additives can improve the working performance of the concrete, making it easier to construct and operate. The entire preparation process is low-alkali. Compared with traditional alkali activators (such as Na2O・nSiO2) that consume a lot of energy and increase CO2 emissions during the production process, this low-alkali thermal activation method reduces the negative impact on the environment to a certain extent. In the production process of building materials, reducing the alkali content helps reduce the risk of alkali-aggregate reaction and improve the durability of concrete. It is also in line with the development trend of green and environmentally friendly building materials and helps reduce carbon emissions in the construction industry.

[0009] Furthermore, the coarse and fine aggregates include coarse aggregates with a particle size of 5mm-25mm and graded sand fine aggregates with a particle size less than 5mm.

[0010] Specifically, coarse aggregate plays the role of skeleton support in concrete. Coarse aggregate with a particle size range of 5mm-25mm can form a stable spatial structure with each other because of its certain particle size and shape, and bear most of the compressive load on the concrete, which helps to improve the bearing capacity of the entire concrete structure, making the prepared concrete more suitable for use in building structural parts that bear large vertical forces, horizontal forces and other loads, such as key stress-bearing parts such as the foundation, columns, and beams of buildings. Coarse aggregate with larger particle size can restrain the shrinkage deformation of concrete during the coagulation and hardening process to a certain extent. Due to its relatively fixed particle spacing and large volume share, it can hinder the transmission of tensile stress generated when the cement paste shrinks, thereby reducing the possibility of shrinkage cracks in concrete, improving the integrity and durability of the concrete structure, and extending the service life of the building.

[0011] Specifically, fine aggregate graded sand can be filled in the gaps formed by the accumulation of coarse aggregates, and work together with cement paste to reduce the porosity inside the concrete and make the structure more compact. With smaller particle sizes, they can better enter the tiny gaps between coarse aggregates, improve the overall density of concrete, and then enhance the physical and mechanical properties of concrete such as compressive strength and impermeability, making it better in terms of waterproofing and moisture resistance. Fine aggregate and graded sand help improve the working performance of concrete, making it easier to operate in construction links such as mixing, transportation, pouring and vibration. They can adjust the fluidity, cohesion and water retention of concrete, avoid segregation, bleeding and other undesirable phenomena in concrete, ensure that concrete can be evenly filled into various parts of the mold or building structure, and ensure construction quality. The combination of graded sand fine aggregate and coarse aggregate, through reasonable particle size distribution, makes the aggregates in the concrete more densely stacked and less porous, further improves the strength and density of concrete, and can also save the amount of cementitious materials to a certain extent, reduce production costs, and also conform to the green environmental protection concept of efficient resource utilization.

[0012] Furthermore, the slag in step S1 is dried at a high temperature of 100-110°C for 24 hours, and the calcination temperature in step S2 is 700-750°C.

[0013] Specifically, continuous drying at a temperature of 100-110°C for 24 hours can effectively remove moisture from the slag. If there is too much moisture in the slag, when mixed with other materials, it will change the mix ratio of the materials, resulting in a decrease in the strength, durability and other properties of the concrete. Excessive moisture will dilute the cement paste, making it unable to fully wrap the aggregate, affecting the adhesion and integrity of the concrete. The high-temperature drying process can also kill impurities such as harmful microorganisms and weed seeds that may exist in the slag. If these impurities exist in concrete, they may damage the concrete structure over time. For example, the growth of microorganisms may cause expansion pressure inside the concrete, causing the generation and expansion of cracks. Continuous high-temperature drying can make the physical and chemical properties of the slag more stable, which helps the slag to participate in the reaction more evenly in subsequent screening, mixing and other steps, ensuring that the performance of the prepared concrete is more consistent and reliable.

[0014] Specifically, mixing the slag powder with sodium hydroxide and calcining it at a temperature of 700-750°C can effectively activate the activity of the slag. Within this temperature range, the mineral components in the slag will undergo changes in crystal structure, breaking and reorganization of chemical bonds, etc., so that the slag can better react with other cementitious materials such as cement, thereby improving the cementitious properties and strength of concrete. High-temperature calcination provides sufficient energy for the chemical reaction between the slag and sodium hydroxide, accelerates the reaction process, and helps to generate more active substances. The calcined slag can better react with components such as sodium silicate in water glass to form a cementitious network with good adhesion and strength. Alkali-aggregate reaction may cause expansion and cracking inside the concrete, seriously affecting the durability of the concrete. By calcining and activating the slag at 700-750°C, the activity of the slag can be guaranteed while reducing the possibility of quality problems caused by excessive alkali in the concrete.

[0015] Further, calculated by mass ratio, the ratio of heat-activated slag-cement-based mixture: water glass: sand fine aggregate: coarse aggregate: water is 1:0.5-0.6:2.4-2.8:1.5-2.0:0.1-0.2.

[0016] Specifically, the appropriate ratio of heat-activated slag-cement-based mixture ensures that slag can be effectively used in concrete. This ratio range allows slag to replace as much traditional cementitious materials as possible, such as cement, without affecting the main properties of concrete, thus realizing the resource utilization of construction slag and reducing the environmental pressure caused by slag landfill. The heat-activated slag-cement-based mixture can cooperate well with other materials within this mass ratio range to exert its cementitious properties. Through mixing with cement and the early heat activation treatment, it can form a stable cementitious network in concrete, wrap aggregates and provide sufficient bonding force, ensure the strength and stability of concrete, and enable it to meet the basic mechanical requirements of building structures.

[0017] Specifically, sodium silicate and other ingredients in water glass can react with the active ingredients in the heat-activated slag-cement-based mixture to further strengthen the cementitious network structure, help improve the early strength of concrete, enable concrete to reach a certain bearing capacity in a shorter period of time, and speed up the construction progress. An appropriate amount of water glass can improve the impermeability and chemical corrosion resistance of concrete. It can fill the tiny pores inside the concrete, prevent the intrusion of moisture and harmful chemicals, thereby extending the service life of the concrete structure and enabling it to maintain good performance even under harsh environmental conditions.

[0018] Specifically, sand as a fine aggregate can fully fill the gaps between coarse and fine aggregates. Sand particles are small and can enter the tiny spaces formed by the accumulation of other aggregates, making the internal structure of concrete more compact, thereby improving the compressive strength and flexural strength of concrete. At the same time, the dense structure also helps to reduce the shrinkage and creep of concrete and improve its dimensional stability. The right amount of sand can improve the working properties of concrete, such as fluidity and cohesion. It can make concrete easier to handle during mixing, transportation and pouring, avoid segregation and bleeding, ensure that the concrete can be evenly distributed in the mold or building structure, and ensure the construction quality.

[0019] Specifically, the coarse and fine aggregates provide good skeleton support for concrete at this ratio. The coarse aggregate bears the main pressure load, while the fine aggregate assists in filling the gaps and transferring stress. Together, they give concrete a higher bearing capacity and can be used to bear larger structural loads, such as the foundation, beams and columns of a building. The appropriate ratio of coarse and fine aggregates helps maintain the volume stability of concrete. They can limit the shrinkage deformation of cement paste during the setting and hardening process, reduce the occurrence of concrete cracks, and improve the integrity and durability of the concrete structure.

[0020] Specifically, water can ensure that the cementitious components in the cement and heat-activated slag-cement-based mixture undergo normal hydration reactions. Sufficient water can fully hydrate the cementitious materials to form hydration products with strength, so that the concrete can obtain the required strength and performance. The right amount of water can adjust the working properties of the concrete, so that the concrete has good working properties and is easy to construct. If the proportion of water is too high, the concrete will be too thin and soft, and segregation and bleeding will occur easily; if the proportion of water is too low, the concrete will be too dry and hard, and it will be difficult to mix and pour.

[0021] Furthermore, when activated slag is mixed with cement to form a slurry, the water-solid ratio is controlled to be 34%-38%, the alkali content is controlled to be 8%-10%; the particle size is less than 1.00mm, and the dry density of slag is 1.4-1.5g / cm 3 .

[0022] Specifically, the water-solid ratio within this range can provide sufficient water for the cementitious materials in the mixed slurry of activated slag and cement, ensuring that the active ingredients in the cement and activated slag undergo sufficient hydration reaction. The appropriate water-solid ratio can enable the cementitious materials to form sufficient hydration products, such as calcium silicate gel, which can fill the gaps between aggregates and bond the aggregates together, thereby giving the concrete strength and stability. This water-solid ratio range helps to optimize the working performance of the slurry, and the slurry can maintain good fluidity and cohesion, facilitating construction operations. If the water-solid ratio is too high, the slurry will become too thin and prone to bleeding, resulting in the separation of the cementitious materials and aggregates in the slurry, affecting the uniformity and strength of the concrete; while if the water-solid ratio is too low, the slurry will be too thick and have poor fluidity, making it difficult to mix evenly with other materials during the mixing process, and is also not conducive to subsequent pouring construction. The appropriate water-solid ratio can control the porosity of the slurry after hardening. When the water-solid ratio is in this range, relatively few pores are generated during the hydration process, and the pore size is also small. Smaller porosity and pore size help improve concrete's impermeability and durability because it is more difficult for moisture and harmful chemicals to penetrate concrete with a denser pore structure.

[0023] Specifically, within this alkali content range, the activity of activated slag can be effectively stimulated. Alkali can destroy the original mineral structure in the slag, causing the components such as silicate to release active silicon ions and aluminum ions. These ions can participate in the subsequent polymerization reaction and form a geopolymer gel structure with other components, thereby improving the gelling properties and strength of concrete. Controlling the alkali content between 6% and 10% can utilize the stimulating effect of alkali to a certain extent, while avoiding excessive alkali content from inducing alkali-aggregate reaction and ensuring the long-term durability of concrete. Alkali content within this range is conducive to promoting the formation of geopolymers. Geopolymer concrete has many excellent properties, such as good frost resistance and strong corrosion resistance. By controlling the alkali content, the activated slag and other materials can be better polymerized to form a geopolymer gel with a three-dimensional network structure, thereby enhancing the comprehensive performance of concrete.

[0024] Specifically, when the particle size of the slag is less than 1.00 mm, the particles are fine and can be dispersed more evenly in the process of mixing with cement to form a slurry, which can make the composition of the slurry more uniform and avoid local agglomeration caused by excessively large particles. At the same time, fine particles can better fill the gaps between other materials, improve the compactness of the slurry, and thus improve the strength and impermeability of concrete. A smaller particle size means that the slag has a larger specific surface area. The larger the specific surface area, the larger the contact area between the slag and alkaline solutions, cement and other materials, and the easier it is for chemical reactions to proceed, which helps to improve the activity activation efficiency of the slag, allowing the slag to participate in the gelation reaction and polymerization reaction faster and more fully, forming a geopolymer concrete with good performance.

[0025] Specifically, the dry density of slag is in the range of 1.4-1.5g / cm³, indicating that the composition and structure of slag are relatively stable. Stable dry density helps to accurately control the amount and mix ratio of materials during the mixing process of pure slurry. If the dry density of slag fluctuates greatly, it will cause a large change in its volume under the same mass of slag, thus affecting the performance stability of pure slurry and concrete. Slag in this dry density range can provide a suitable filling effect when mixed with other materials. The density of slag and the density of other materials (such as cement and aggregate) cooperate with each other to effectively fill the voids inside the concrete. Appropriate filling can reduce the pores inside the concrete, improve the density and strength of the concrete, and also help improve the working performance and durability of the concrete.

[0026] Furthermore, the added materials include fly ash and ground granulated blast furnace slag, the fly ash particle size is less than 45 μm, and the specific surface area is 400 m2 / kg-450 m 2 / kg, the particle size of ground granulated blast furnace slag is less than 45μm, and the specific surface area is 500m² / kg-520m² / kg.

[0027] Specifically, the particle size of fly ash is less than 45μm, which can be well filled in the pores of concrete. Due to its small particle size, it can enter the tiny gaps between other materials (such as cement particles and aggregates), making the internal structure of concrete more compact, thereby improving the compressive strength and impermeability of concrete. The specific surface area of ​​fly ash is 400m² / kg-450m² / kg, and the larger specific surface area makes it more chemically active. The active silica and alumina in fly ash can react with calcium hydroxide produced by cement hydration to produce more gelling substances, such as calcium silicate gel, etc., further enhancing the gelling properties of concrete and improving the later strength of concrete. Fly ash is an industrial by-product produced by thermal power generation. Adding it to concrete as an additive effectively solves the problem of fly ash treatment, avoids soil and water pollution caused by fly ash stacking, realizes the resource utilization of industrial waste, and conforms to the concept of environmental protection and sustainable development.

[0028] Specifically, the particle size of ground granulated blast furnace slag is less than 45μm, which can effectively fill the internal voids of concrete and make the concrete more compact. At the same time, its smaller particle size helps to improve the working properties of concrete, such as fluidity and cohesion. During the concrete mixing process, it can make the concrete more uniform, facilitate construction operations, and reduce segregation and bleeding. The specific surface area of ​​ground granulated blast furnace slag is 500m² / kg-520m² / kg, and the large specific surface area enables it to react quickly in an alkaline environment. It can be used as a high-quality substitute for cementitious materials. When reacting with alkaline activators (such as sodium hydroxide) and other active materials (such as thermally activated slag), it can generate geopolymer gel. This gel structure has good adhesion and strength, and can improve the frost resistance and corrosion resistance of concrete. Ground granulated blast furnace slag is a by-product of the metal smelting industry. Using it in concrete realizes the reuse of industrial waste slag, reduces the pressure of waste slag on the environment, and also reduces the dependence on traditional cementitious materials (such as cement) in the concrete production process, saving natural resources.

[0029] Furthermore, the fly ash is Class F fly ash, the ground granulated blast furnace slag is S105 ground granulated blast furnace slag, Class F fly ash accounts for 1%-2% of the total mass of the neat paste, water, and coarse and fine aggregates, and the S105 ground granulated blast furnace slag accounts for 4%-6% of the total mass of the neat paste, water, and coarse and fine aggregates.

[0030] Specifically, when the proportion of Class F fly ash is 1%-2%, it can effectively improve the working performance of concrete. Due to its fine particles, it can play a lubricating role in the concrete mixing process, enhance the fluidity of the concrete, and help the concrete better fill the corners of the mold or building structure during the pouring process, avoiding voids or uneven filling, and ensuring the quality of concrete construction.

[0031] Specifically, within this proportion range, Class F fly ash can participate in the hydration reaction of cement. The active silica and alumina it contains can react with calcium hydroxide generated by cement hydration to generate additional gelling substances, such as calcium silicate gel. This secondary hydration reaction helps to improve the later strength of concrete, so that the strength of concrete continues to increase over a long period of time, and enhances the bearing capacity of concrete structures. An appropriate amount of Class F fly ash can reduce the porosity of concrete. Its fine particles fill the pores of concrete, and the gelling substances generated by the secondary hydration reaction also help to refine the pore structure, thereby improving the impermeability and chemical corrosion resistance of concrete. This can effectively extend the service life of concrete structures in harsh environments. As an industrial waste, Class F fly ash has a relatively low cost. Adding Class F fly ash accounting for 1%-2% of the total mass of pure slurry, water, and coarse and fine aggregates to concrete can replace part of the cement to a certain extent, thereby reducing the production cost of concrete.

[0032] Specifically, S105 ground granulated blast furnace slag has high activity and can significantly improve the strength of concrete when it accounts for 4%-6% of the total mass of the pure slurry, water, and coarse and fine aggregates. It can react quickly in an alkaline environment to generate geopolymer gel. This gel structure can enhance the bonding and cohesion of concrete, significantly improve the compressive and flexural strength of concrete, and meet the demand for high-strength materials for building structures.

[0033] Specifically, the addition of S105 ground granulated blast furnace slag helps to improve the durability of concrete. The geopolymer gel generated by its reaction can fill the pores inside the concrete, improve the density of the concrete, and enhance the concrete's resistance to adverse factors such as freeze-thaw cycles and chemical erosion. For example, in cold areas, it can reduce the structural damage of concrete caused by freeze-thaw cycles; in environments with risks of chemical corrosion, it can prevent the invasion of harmful substances. Within this proportion range, S105 ground granulated blast furnace slag can adjust the working performance of concrete. Its fine particles can make the concrete more cohesive, reduce the segregation of concrete during transportation and construction, ensure the uniformity of concrete, and facilitate construction operations.

[0034] Specifically, Class F fly ash and S105 ground granulated blast furnace slag work together in concrete to play a synergistic role. Class F fly ash mainly plays a role in improving working performance and partial strength in the early stage, while S105 ground granulated blast furnace slag performs outstandingly in terms of strength growth and durability improvement in the middle and late stages. The combination of the two can enable concrete to maintain good performance at different stages, and comprehensively improve the working performance, strength and durability of concrete.

[0035] Furthermore, the additives also include at least three of carbon fiber, steel fiber, waste shell powder, rubber powder, glass fiber, retarder, and water reducer, the carbon fiber accounts for 0.5%-0.8% of the total mass of the neat paste, water, and coarse and fine aggregate, the steel fiber accounts for 1%-1.5% of the total mass of the neat paste, water, and coarse and fine aggregate, the waste shell powder accounts for 0.5%-1.5% of the total mass of the neat paste, water, and coarse and fine aggregate, the rubber powder accounts for 1%-1.5% of the total mass of the neat paste, water, and coarse and fine aggregate, the glass fiber accounts for 0.5%-1.0% of the total mass of the neat paste, water, and coarse and fine aggregate, the retarder accounts for 0.1%-0.3% of the total mass of the neat paste, water, and coarse and fine aggregate, and the water reducer accounts for 0.3%-0.5% of the total mass of the neat paste, water, and coarse and fine aggregate.

[0036] Specifically, the steel fibers include wavy steel fibers or fine steel fibers with a diameter between 0.1-0.3 mm. The wavy steel fibers can increase the contact area with the cement base material and improve the bonding force. The fine steel fibers play the role of bridging cracks in concrete. When the concrete is subjected to tension, the steel fibers can bear part of the tension and prevent the expansion of the cracks. When accounting for 1%-1.5% of the total mass of the net paste, water, and coarse and fine aggregates, the steel fibers can effectively improve the tensile strength of the concrete. In some bending members such as beams and slab structures, the addition of steel fibers can significantly enhance the ability of concrete to resist bending and tensile damage, allowing the structure to withstand greater loads without brittle fracture.

[0037] Specifically, when the concrete structure is subjected to shear force, steel fibers can resist shear deformation through bonding with the concrete matrix. This is very important for structural components such as columns and shear walls that are subjected to large horizontal shear forces. Adding an appropriate amount of steel fibers can significantly improve the shear resistance of concrete and enhance the stability of the structure under horizontal forces such as earthquakes and wind loads. The presence of steel fibers gives concrete better toughness and can absorb more impact energy. Steel fiber concrete resists impact, reduces damage and spalling on the concrete surface, and extends the service life of the structure. Because steel fibers can limit the development of cracks, they can reduce the intrusion of harmful substances such as moisture and chloride ions, thereby reducing the risk of durability problems such as steel corrosion and freeze-thaw damage in concrete.

[0038] Specifically, in some harsh environmental conditions, such as marine environment, chemical corrosion environment, etc., steel fiber concrete can better maintain the integrity of the structure. Because it improves the mechanical properties of concrete, it also indirectly enhances the resistance of the structure to environmental erosion, so that the concrete structure can maintain good performance during long-term use. Steel fibers accounting for 1%-1.5% of the total mass of the net slurry, water, and coarse and fine aggregates can provide sufficient restraint. Because the steel fibers are tightly bonded to the concrete matrix, the relative displacement of the internal particles of the concrete is limited, thereby reducing the structural deformation and even cracking caused by shrinkage and creep. The right amount of steel fibers can be evenly distributed during the concrete mixing process, and will not cause a significant deterioration in the working performance of the concrete. Moreover, during the concrete pouring process, steel fibers can help maintain the shape stability of the concrete, prevent local collapse or excessive deformation of the concrete during the vibration process, and ensure the smooth progress of the concrete construction.

[0039] Specifically, in the long run, adding steel fibers will improve the mechanical properties and durability of concrete, reduce the number of repairs and reinforcements during the use of the structure, and thus reduce the cost of the entire life cycle. Using steel fibers at a ratio of 1%-1.5% of the total mass of the net slurry, water, and coarse and fine aggregates can give full play to its reinforcing effect without significantly increasing the amount of steel fibers, achieving the purpose of economical and rational use of resources, so that the concrete can meet the performance requirements while reducing costs as much as possible.

[0040] Specifically, carbon fiber includes polyacrylonitrile-based carbon fiber or asphalt-based carbon fiber, and carbon fiber has excellent mechanical properties such as ultra-high strength and modulus. Carbon fiber evenly dispersed in concrete can effectively share the load borne by concrete like "tendons and bones", and significantly improve the mechanical performance indicators of concrete such as tensile strength, flexural strength and impact toughness. In the case where the structure is subjected to tension, bending or impact, carbon fiber can inhibit the generation and expansion of cracks, enhance the overall toughness of the concrete structure, and make the structure more durable, especially suitable for some construction projects with high requirements for earthquake resistance and impact resistance. The addition of carbon fiber can also improve the durability and stability of concrete. It can prevent the intrusion of external corrosive media such as chloride ions and sulfates to a certain extent, and delay the deterioration process of concrete. At the same time, due to its good chemical stability, it can also maintain its own performance stability under complex environmental conditions, thereby improving the long-term service capacity of the entire concrete structure, reducing the number of repairs and replacements, and reducing the cost of the entire life cycle.

[0041] Specifically, the waste shell powder includes oyster shells and scallop shells. Specifically, the collected shells are first soaked and cleaned with an alkaline solution. Soaking the shells in a sodium hydroxide solution can effectively remove dirt, algae and organic residues on the surface of the shells, improve the purity of the shells and the effect of subsequent treatment. The concentration of the alkaline solution is 1M / L, and the soaking time is 1-2 hours to avoid damage to the shell structure and ensure effective cleaning. Then the cleaned shells are broken into shell particles and dried. The broken shells are easy to grind and process. Drying is to remove moisture from the shells to prevent agglomeration during the grinding process or uneven thermal expansion in subsequent processing. The broken shell particles are dried to ensure that the moisture content in the shell particles is minimized. The shell particles are ground into shell powder by ball milling; ball milling can grind the shell particles into fine powder, increase the specific surface area of ​​the shell powder, and improve its dispersibility and reactivity in the composite material. Calcine at a temperature of 800°C to 1000°C for 2 hours and set aside. High-temperature calcination can completely remove organic matter in the shells, such as proteins and carbohydrates, and at the same time convert the calcium carbonate in the shells into calcium oxide, thereby improving the chemical and thermal stability of the shell powder.

[0042] Specifically, the preparation method of shell powder effectively improves the purity, fineness and stability of shell powder through the steps of soaking and cleaning, crushing and drying, ball milling and calcining. The spare discarded shell powder particles can play a certain lubricating role in the mixing process of materials such as concrete, improve the fluidity of the material, and facilitate construction operations. It can be filled in the tiny gaps between cement particles and aggregates to make the internal structure of the material more compact, which helps to improve the compressive strength and impermeability of the material. In addition, the discarded shell powder comes from shell waste, and it is used as a reinforcing agent to realize the reuse of waste resources and reduce the pollution of shell garbage to the environment, which is in line with the concept of sustainable development and environmental protection. Shell powder contains ingredients such as calcium carbonate. In an alkaline environment, it may react with cement hydration products to generate some substances with gelling properties, further enhancing the overall strength of the material.

[0043] Specifically, the rubber powder used is 80 mesh tire rubber powder, which can reduce resource waste while having good elasticity and toughness. After being added to the material, when the material is impacted by external force, the rubber powder can absorb and disperse the impact energy through its own elastic deformation, effectively improving the material's impact resistance, making it less likely to crack, break, or be damaged by sudden impact. It can give the material a certain degree of flexibility, reduce the brittleness of the material, and make the material less likely to have brittle fracture when it is deformed under load, but have a certain degree of elastic deformation ability.

[0044] Specifically, glass fiber includes alkali-resistant glass fiber or short-cut glass fiber, which has high strength and modulus. After being added to the material, it can bear part of the load like "muscles and bones", significantly improving the tensile strength, flexural strength, etc. of the material. In concrete, glass fiber can effectively resist the expansion of cracks caused by tension, making the material less likely to be damaged when subjected to loads such as bending and stretching, and enhancing the overall bearing capacity of the structure. It can form a randomly distributed fiber reinforcement network inside the material. When the material has microcracks due to shrinkage, temperature changes or stress, the glass fiber can cross the cracks to prevent further expansion of the cracks, improve the material's crack resistance, and ensure the integrity and durability of the material structure. Due to the inhibitory effect of glass fiber on crack expansion, the channels for external harmful substances (such as moisture, chemically corrosive substances, etc.) to invade the material through cracks are reduced, thereby enhancing the material's resistance to environmental erosion and extending the service life of the material. The presence of glass fiber can constrain the relative displacement of particles inside the material, help reduce shrinkage deformation, creep and other phenomena during the hardening process of the material, improve the dimensional stability of the material, and ensure that the structure will not affect its function due to excessive deformation during long-term use.

[0045] Specifically, the retarder includes one of calcium ethylenediaminetetramethylenephosphonate, sodium carboxymethylcellulose, and sodium gluconate, and the retarder can delay the coagulation and hardening process of the material. During the construction of some large-scale projects or in high-temperature environments, materials such as concrete may coagulate too quickly, resulting in difficulties in construction operations. After adding the retarder, the initial and final setting times of the material can be appropriately extended according to actual construction needs, so that construction personnel have more time to perform operations such as mixing, transportation, pouring, and vibration to ensure construction quality. The retarder slows down the hydration rate of cement, making the heat release smoother, reducing the possibility of cracks in the concrete due to temperature stress, and improving the integrity and durability of large-volume concrete structures.

[0046] Specifically, the water reducer includes calcium lignin sulfonate, a polycarboxylic acid water reducer with a main chain of methacrylic acid and methyl acrylate copolymer and a side chain of polyoxyethylene. The water reducer can reduce the water-binder ratio in the concrete material, and reduce the amount of water while maintaining the same fluidity. It can effectively avoid the adverse phenomena of material segregation, water seepage, etc., and ensure the uniformity and quality of construction.

[0047] Specifically, water reducers reduce the water-cement ratio, which reduces the porosity inside the material and makes the structure more compact. After cement and other cementitious materials are hydrated, more and denser hydration products can be formed, thereby improving the mechanical properties of the material such as compressive strength and flexural strength. By reducing the channels for external moisture and chemically corrosive substances to enter the material, the material's resistance to durability problems such as freeze-thaw cycles and chemical corrosion is enhanced, the service life of the material is extended, and its stability for long-term use under different environmental conditions is improved. On the basis of maintaining the working performance and strength requirements of the material, the use of water reducers can appropriately reduce the amount of cement used, which not only helps to reduce production costs, but also reduces the consumption of natural resources and the emission of pollutants such as carbon dioxide during cement production.

[0048] Furthermore, the ratio of heat-activated slag:cement:sodium hydroxide powder in the heat-activated slag-cement-based mixture is 1:1:0.04-0.05.

[0049] Specifically, the heat-activated slag and cement are mixed in a 1:1 ratio, which can give full play to the advantages of both. Cement is a traditional cementitious material with high early strength and good bonding properties. After being processed, the heat-activated slag also has certain cementing properties, and it contains rich aluminosilicate components. Combining the two, the heat-activated slag can supplement part of the cementing function of cement, and at the same time, the early strength advantage of cement can make up for the possible lack of early strength of the heat-activated slag, so that the concrete can have better strength development in both the early and late stages.

[0050] Specifically, since the cost of slag is relatively low, mixing it with cement in a 1:1 ratio can reduce the production cost of concrete to a certain extent. At the same time, this mixing method can reduce the demand for cement. For large-scale construction projects, it can save a lot of material costs while ensuring quality. The cement production process produces a large amount of carbon dioxide and consumes a lot of natural resources. By using heat-activated slag to replace part of the cement in a 1:1 ratio, the amount of cement used can be reduced, thereby reducing carbon emissions in the concrete production process and reducing the negative impact on the environment.

[0051] Specifically, sodium hydroxide, as an activator, can effectively activate the activity of slag within this ratio range. It can destroy the original mineral structure in the slag, so that the components such as silicate release active silicon ions and aluminum ions. These ions can participate in the subsequent gelling reaction, and together with cement and other components, form a stable gelling network structure, thereby improving the strength and durability of concrete. A lower sodium hydroxide ratio can activate the activity of slag while avoiding alkali-aggregate reaction caused by excessive alkali content. Alkali-aggregate reaction can cause expansion, cracking and other problems inside the concrete, seriously affecting the durability of the concrete. At this ratio, the amount of alkali can be effectively controlled, and while exerting its stimulating effect, the long-term performance stability of the concrete can be guaranteed.

[0052] Furthermore, another object of the present invention is to provide a prefabricated steel column made of concrete obtained by the method for preparing low-alkali heat-activated slag-cement-based mixed geopolymer concrete.

[0053] Specifically, due to the use of low-alkali heat-activated slag-cement-based mixed geopolymer concrete, this concrete itself combines the advantages of multiple materials such as heat-activated slag, cement, water glass, and coarse and fine aggregates. The gelling network structure formed by the heat-activated slag and cement-based mixture can effectively bond the aggregates together. In prefabricated steel columns, this structure can better withstand a variety of complex load combinations such as axial pressure, bending moment and shear force. In high-rise buildings, steel columns are subjected to huge vertical gravity loads and horizontal forces under wind loads or earthquakes. The use of this high-performance concrete can ensure that the columns have sufficient bearing capacity and improve the structural safety of the building.

[0054] Specifically, the geopolymer concrete in the prefabricated steel column has good toughness and can absorb energy better than traditional concrete during the stress process. This is because the cementitious material properties of geopolymer concrete enable the internal structure to deform to a certain extent without sudden brittle failure when subjected to external forces. This toughness works in synergy with the steel frame to effectively reduce the deformation of the column and prevent the collapse of the structure when the column is subjected to a large lateral force. In the concrete preparation process, the low-alkali thermal activation method is adopted, which effectively reduces energy consumption and carbon emissions compared to the large amount of energy consumption and carbon dioxide generation in the traditional concrete production process. The prefabricated steel column is made of this special concrete, and the quality and pouring process of the concrete can be better controlled during the prefabrication process in the factory. Compared with on-site casting, the prefabricated components have higher dimensional accuracy and more stable quality, which can effectively reduce the time and difficulty of on-site construction. At the same time, prefabricated steel columns can be standardized in factories to improve production efficiency and reduce production costs.

[0055] Due to the good durability of prefabricated steel columns, the number of repairs and reinforcements required due to structural damage is reduced during their service life. This not only reduces the maintenance cost of the building, but also avoids the impact on the use function of the building caused by repairs and reinforcement work, which has significant economic benefits in the long run.

[0056] Compared with the prior art, the present invention has the following advantages: 1. The present invention prepares components by mixing heat-activated slag and ordinary cement and adding alkali-activated materials, which can effectively realize the application of slag-cement-based polymer concrete prefabricated steel frame columns. In combination with prefabricated beam-column nodes, the assembled construction of the combined structure can be realized, thereby realizing the recycling of solid waste materials.

[0057] 2. The present invention greatly reduces the reliance on traditional cement by adding heat-activated slag to traditional cement, reduces carbon emissions from raw material production, and responds to the national call for energy conservation and emission reduction; using activated slag to replace 50% of cement can achieve higher concrete strength, reduce total energy consumption by about 30%, and reduce carbon dioxide generation by about 40%. By adjusting the mix ratio and relying on strength and durability indicators, the application scenarios can be further expanded. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 It is a schematic diagram of Von-Mise analysis of the steel-concrete column of the present invention.

[0059] Figure 2 It is a schematic diagram of concrete compressive damage analysis according to the present invention.

[0060] Figure 3 It is a schematic diagram of Von-Mise analysis of the cross-shaped steel column of the present invention.

[0061] Figure 4 It is a schematic diagram of Von-Mise analysis of steel bars in a column according to the present invention.

[0062] Figure 5 It is a schematic diagram of the decomposition of the prefabricated steel column of the present invention.

[0063] Figure 6 It is a schematic diagram of the prefabricated steel column of the present invention. DETAILED DESCRIPTION

[0064] In order to make those skilled in the art more clearly understand the technical solution of the present invention, the following examples are listed for illustration. Unless otherwise specified, the raw materials, reagents or devices used in the following embodiments can be obtained from conventional commercial channels or can be obtained by existing known methods.

[0065] The present invention will be further described below in conjunction with specific embodiments: A method for preparing low-alkali heat-activated slag-cement-based mixed geopolymer concrete comprises the following steps: S1. Take soil from the project excavation as raw material slag, and dry the taken slag through drying equipment; S2, the slag in step S1 is screened and divided into slag powder and crushed stone particles, the slag powder is mixed with sodium hydroxide, activated by heat treatment and calcination, and then mixed with cement to form a heat-activated slag-cement-based mixture, and the crushed stone particles are separated to obtain coarse and fine aggregates; S3, mixing the heat-activated slag-cement-based mixture and water glass to form a slurry; S4. Mix the pure paste with water, coarse and fine aggregates and external materials to form concrete.

[0066] Coarse and fine aggregates include coarse aggregate with a particle size of 5mm-25mm and graded sand fine aggregate with a particle size less than 5mm.

[0067] The slag in step S1 is dried at a high temperature of 100-110°C for 24 hours, and the calcination temperature in step S2 is 700-750°C.

[0068] Calculated by mass ratio, the ratio of heat-activated slag-cement-based mixture: water glass: sand fine aggregate: coarse aggregate: water is 1:0.5-0.6:2.4-2.8:1.5-2.0:0.1-0.2.

[0069] When activated slag is mixed with cement, the water-solid ratio is controlled to be 34%-38%, the alkali content is 8%-10%; the particle size is less than 1.00mm, and the dry density of slag is 1.4-1.5g / cm 3。

[0070] The added materials include fly ash and ground granulated blast furnace slag. The particle size of fly ash is less than 45μm and the specific surface area is 400m² / kg-450m 2 / kg, the particle size of ground granulated blast furnace slag is less than 45μm, and the specific surface area is 500m² / kg-520m² / kg.

[0071] The fly ash is Class F fly ash, and the ground granulated blast furnace slag is S105 ground granulated blast furnace slag. Class F fly ash accounts for 1%-2% of the total mass of the neat paste, water, and coarse and fine aggregates, and S105 ground granulated blast furnace slag accounts for 4%-6% of the total mass of the neat paste, water, and coarse and fine aggregates.

[0072] The added materials also include at least three of carbon fiber, steel fiber, waste shell powder, rubber powder, glass fiber, retarder and water reducer. The carbon fiber accounts for 0.5%-0.8% of the total mass of the neat paste, water and coarse and fine aggregates, the steel fiber accounts for 1%-1.5% of the total mass of the neat paste, water and coarse and fine aggregates, the waste shell powder accounts for 0.5%-1.5% of the total mass of the neat paste, water and coarse and fine aggregates, the rubber powder accounts for 1%-1.5% of the total mass of the neat paste, water and coarse and fine aggregates, the glass fiber accounts for 0.5%-1.0% of the total mass of the neat paste, water and coarse and fine aggregates, the retarder accounts for 0.1%-0.3% of the total mass of the neat paste, water and coarse and fine aggregates, and the water reducer accounts for 0.3%-0.5% of the total mass of the neat paste, water and coarse and fine aggregates.

[0073] The steel fibers include corrugated steel fibers or fine steel fibers with a diameter between 0.1 and 0.3 mm.

[0074] The carbon fibers include polyacrylonitrile-based carbon fibers or pitch-based carbon fibers with a diameter of 5-10 μm.

[0075] Waste shell powder includes oyster shells and scallop shells. The collected shells are first soaked and cleaned in 1M / L NaOH alkaline solution for 12 hours, and then the cleaned shells are broken into 200 mesh shell particles, dried, and ground into shell powder by ball milling. The powder is calcined at 800°C for 2 hours and set aside.

[0076] The rubber powder used is 80 mesh tire rubber powder processed by Shengfei Minerals.

[0077] The glass fibers include alkali-resistant glass fibers or chopped glass fibers having a diameter of 5-20 mm.

[0078] The retarder includes one of calcium ethylenediaminetetramethylenephosphonate, sodium carboxymethylcellulose and sodium gluconate.

[0079] The water reducing agent includes calcium lignin sulfonate, a polycarboxylic acid water reducing agent whose main chain is composed of a copolymer of methacrylic acid and methyl acrylate and whose side chain is polyoxyethylene.

[0080] The ratio of heat-activated slag: cement: sodium hydroxide powder in the heat-activated slag-cement-based mixture is 1:1:0.04-0.05.

[0081] Example 1 A method for preparing low-alkali heat-activated slag-cement-based mixed geopolymer concrete comprises the following steps: S1. Take soil from the project excavation as raw material slag, and dry the taken slag through drying equipment; S2, the slag in step S1 is screened and divided into slag powder and crushed stone particles, the slag powder is mixed with sodium hydroxide, activated by heat treatment and calcination, and then mixed with cement to form a heat-activated slag-cement-based mixture, and the crushed stone particles are separated to obtain coarse and fine aggregates; S3, mixing the heat-activated slag-cement-based mixture and water glass to form a slurry; S4. Mix the pure paste with water, coarse and fine aggregates and external materials to form concrete.

[0082] The coarse and fine aggregates include coarse aggregate with a particle size of 5mm and graded sand fine aggregate with a particle size of 3mm.

[0083] The slag in step S1 is dried at a high temperature of 100°C for 24 hours, and the calcination temperature in step S2 is 750°C.

[0084] Calculated by mass ratio, the ratio of heat-activated slag-cement-based mixture: water glass: sand fine aggregate: coarse aggregate: water is 1:0.6:2.8:2.0:0.1.

[0085] When activated slag is mixed with cement, the water-solid ratio is controlled to be 34%, the alkali content is 8%; the particle size is 0.80mm, and the dry density of slag is 1.5g / cm 3。

[0086] The added materials include fly ash and ground granulated blast furnace slag. The fly ash has a particle size of 40 μm and a specific surface area of ​​400 m² / kg. The ground granulated blast furnace slag has a particle size of 35 μm and a specific surface area of ​​500 m² / kg.

[0087] The fly ash is Class F fly ash, and the ground granulated blast furnace slag is S105 ground granulated blast furnace slag. Class F fly ash accounts for 1% of the total mass of the neat paste, water, and coarse and fine aggregates, and S105 ground granulated blast furnace slag accounts for 4% of the total mass of the neat paste, water, and coarse and fine aggregates.

[0088] The added materials also include carbon fiber, steel fiber, waste shell powder, rubber powder, glass fiber, and water reducer. The carbon fiber accounts for 0.8% of the total mass of the neat paste, water, and coarse and fine aggregates; the steel fiber accounts for 1.5% of the total mass of the neat paste, water, and coarse and fine aggregates; the waste shell powder accounts for 1.0% of the total mass of the neat paste, water, and coarse and fine aggregates; the rubber powder accounts for 1% of the total mass of the neat paste, water, and coarse and fine aggregates; the glass fiber accounts for 0.5% of the total mass of the neat paste, water, and coarse and fine aggregates; and the water reducer accounts for 0.3% of the total mass of the neat paste, water, and coarse and fine aggregates.

[0089] The steel fibers include fine steel fibers with a diameter between 0.1 and 0.3 mm.

[0090] The carbon fibers include polyacrylonitrile-based carbon fibers having a diameter of 5 μm.

[0091] The glass fiber is an alkali-resistant glass fiber with a diameter of 20 mm.

[0092] The water reducer is a kind of polycarboxylic acid water reducer with the main chain being a copolymer of methacrylic acid and methyl acrylate and the side chain being polyoxyethylene.

[0093] The ratio of heat-activated slag:cement:sodium hydroxide powder in the heat-activated slag-cement-based mixture is 1:1:0.04.

[0094] Example 2 A method for preparing low-alkali heat-activated slag-cement-based mixed geopolymer concrete comprises the following steps: S1. Take soil from the project excavation as raw material slag, and dry the taken slag through drying equipment; S2, the slag in step S1 is screened and divided into slag powder and crushed stone particles, the slag powder is mixed with sodium hydroxide, activated by heat treatment and calcination, and then mixed with cement to form a heat-activated slag-cement-based mixture, and the crushed stone particles are separated to obtain coarse and fine aggregates; S3, mixing the heat-activated slag-cement-based mixture and water glass to form a slurry; S4. Mix the pure paste with water, coarse and fine aggregates and external materials to form concrete.

[0095] The coarse and fine aggregates include coarse aggregate with a particle size of 25 mm and graded sand fine aggregate with a particle size of 4 mm.

[0096] The slag in step S1 is dried at a high temperature of 110°C for 24 hours, and the calcination temperature in step S2 is 750°C.

[0097] Calculated by mass ratio, the ratio of heat-activated slag-cement-based mixture: water glass: sand fine aggregate: coarse aggregate: water is 1:0.6:2.4:1.5:0.1.

[0098] When activated slag is mixed with cement, the water-solid ratio is controlled to be 38%, the alkali content is 10%; the particle size is 0.90mm, and the dry density of slag is 1.4g / cm 3。

[0099] The added materials include fly ash and ground granulated blast furnace slag. The fly ash particle size is 35μm and the specific surface area is 400m² / kg. The ground granulated blast furnace slag particle size is 40μm and the specific surface area is 500m² / kg.

[0100] The fly ash is Class F fly ash, and the ground granulated blast furnace slag is S105 ground granulated blast furnace slag. Class F fly ash accounts for 2% of the total mass of the neat paste, water, and coarse and fine aggregates, and S105 ground granulated blast furnace slag accounts for 6% of the total mass of the neat paste, water, and coarse and fine aggregates.

[0101] The added materials also include carbon fiber, steel fiber, rubber powder, glass fiber and water reducer, wherein the carbon fiber accounts for 0.8% of the total mass of the neat paste, water and coarse and fine aggregates, the steel fiber accounts for 1.5% of the total mass of the neat paste, water and coarse and fine aggregates, the rubber powder accounts for 1.5% of the total mass of the neat paste, water and coarse and fine aggregates, the glass fiber accounts for 1.0% of the total mass of the neat paste, water and coarse and fine aggregates, and the water reducer accounts for 0.5% of the total mass of the neat paste, water and coarse and fine aggregates.

[0102] The steel fiber is a corrugated steel fiber with a diameter of 0.3 mm.

[0103] The carbon fiber is asphalt-based carbon fiber with a diameter of 10 μm.

[0104] The glass fibers were chopped glass fibers with a diameter of 20 mm.

[0105] The water reducing agent is calcium lignin sulfonate.

[0106] The ratio of heat-activated slag:cement:sodium hydroxide powder in the heat-activated slag-cement-based mixture is 1:1:0.04.

[0107] Example 3 A method for preparing low-alkali heat-activated slag-cement-based mixed geopolymer concrete comprises the following steps: S1. Take soil from the project excavation as raw material slag, and dry the taken slag through drying equipment; S2, the slag in step S1 is screened and divided into slag powder and crushed stone particles, the slag powder is mixed with sodium hydroxide, activated by heat treatment and calcination, and then mixed with cement to form a heat-activated slag-cement-based mixture, and the crushed stone particles are separated to obtain coarse and fine aggregates; S3, mixing the heat-activated slag-cement-based mixture and water glass to form a slurry; S4. Mix the pure paste with water, coarse and fine aggregates and external materials to form concrete.

[0108] The coarse and fine aggregates include coarse aggregate with a particle size of 5 mm and graded sand fine aggregate with a particle size of 2 mm.

[0109] The slag in step S1 is dried at a high temperature of 100°C for 24 hours, and the calcination temperature in step S2 is 700°C.

[0110] Calculated by mass ratio, the ratio of heat-activated slag-cement-based mixture: water glass: sand fine aggregate: coarse aggregate: water is 1:0.5:2.8:2.0:0.1.

[0111] When activated slag is mixed with cement, the water-solid ratio is controlled to be 34%, the alkali content is controlled to be 8%; the particle size is 0.70mm, and the dry density of slag is 1.4g / cm 3。

[0112] The added materials include fly ash and ground granulated blast furnace slag. The fly ash particle size is 40 μm and the specific surface area is 450 m 2 / kg, the particle size of ground granulated blast furnace slag is less than 40μm, and the specific surface area is 520m² / kg.

[0113] The fly ash is Class F fly ash, and the ground granulated blast furnace slag is S105 ground granulated blast furnace slag. Class F fly ash accounts for 1% of the total mass of the neat paste, water, and coarse and fine aggregates, and S105 ground granulated blast furnace slag accounts for 6% of the total mass of the neat paste, water, and coarse and fine aggregates.

[0114] The added materials also include steel fiber, waste shell powder and retarder, wherein the steel fiber accounts for 1.5% of the total mass of the neat paste, water and coarse and fine aggregates, the waste shell powder accounts for 0.5% of the total mass of the neat paste, water and coarse and fine aggregates, and the retarder accounts for 0.3% of the total mass of the neat paste, water and coarse and fine aggregates.

[0115] The steel fiber is a fine steel fiber with a diameter of 0.3 mm.

[0116] The retarder is sodium carboxymethyl cellulose.

[0117] The ratio of heat-activated slag:cement:sodium hydroxide powder in the heat-activated slag-cement-based mixture is 1:1:0.05.

[0118] Example 4 A method for preparing low-alkali heat-activated slag-cement-based mixed geopolymer concrete comprises the following steps: S1. Take soil from the project excavation as raw material slag, and dry the taken slag through drying equipment; S2, the slag in step S1 is screened and divided into slag powder and crushed stone particles, the slag powder is mixed with sodium hydroxide, activated by heat treatment and calcination, and then mixed with cement to form a heat-activated slag-cement-based mixture, and the crushed stone particles are separated to obtain coarse and fine aggregates; S3, mixing the heat-activated slag-cement-based mixture and water glass to form a slurry; S4. Mix the pure paste with water, coarse and fine aggregates and external materials to form concrete.

[0119] The coarse and fine aggregates include coarse aggregate with a particle size of 15 mm and graded sand fine aggregate with a particle size of 4.5 mm.

[0120] The slag in step S1 is dried at a high temperature of 110°C for 24 hours, and the calcination temperature in step S2 is 700°C.

[0121] Calculated by mass ratio, the ratio of heat-activated slag-cement-based mixture: water glass: sand fine aggregate: coarse aggregate: water is 1:0.5:2.4:1.5:0.1.

[0122] When activated slag is mixed with cement, the water-solid ratio is controlled to be 38%, the alkali content is 10%; the particle size is 0.60mm, and the dry density of slag is 1.4g / cm 3。

[0123] The added materials include fly ash and ground granulated blast furnace slag. The fly ash particle size is 25μm and the specific surface area is 400m² / kg. The ground granulated blast furnace slag particle size is 35μm and the specific surface area is 520m² / kg.

[0124] The fly ash is Class F fly ash, and the ground granulated blast furnace slag is S105 ground granulated blast furnace slag. Class F fly ash accounts for 2% of the total mass of the neat paste, water, and coarse and fine aggregates, and S105 ground granulated blast furnace slag accounts for 4% of the total mass of the neat paste, water, and coarse and fine aggregates.

[0125] The additives also include carbon fiber, steel fiber, waste shell powder, rubber powder, glass fiber, and water reducing agent. The carbon fiber accounts for 0.5% of the total mass of the pure slurry, water, and coarse and fine aggregates, the steel fiber accounts for 1.5% of the total mass of the pure slurry, water, and coarse and fine aggregates, the waste shell powder accounts for 1.5% of the total mass of the pure slurry, water, and coarse and fine aggregates, the rubber powder accounts for 1.5% of the total mass of the pure slurry, water, and coarse and fine aggregates, the glass fiber accounts for 1.0% of the total mass of the pure slurry, water, and coarse and fine aggregates, and the water reducing agent accounts for 0.5% of the total mass of the pure slurry, water, and coarse and fine aggregates. The steel fiber is a wavy steel fiber with a diameter of 0.1 mm.

[0126] The carbon fiber is asphalt-based carbon fiber with a diameter of 5 μm.

[0127] The glass fiber is an alkali-resistant glass fiber with a diameter of 20 mm.

[0128] The water reducing agent is calcium lignin sulfonate.

[0129] The ratio of heat-activated slag:cement:sodium hydroxide powder in the heat-activated slag-cement-based mixture is 1:1:0.04.

[0130] Example 5 A method for preparing low-alkali heat-activated slag-cement-based mixed geopolymer concrete comprises the following steps: S1. Take soil from the project excavation as raw material slag, and dry the taken slag through drying equipment; S2, the slag in step S1 is screened and divided into slag powder and crushed stone particles, the slag powder is mixed with sodium hydroxide, activated by heat treatment and calcination, and then mixed with cement to form a heat-activated slag-cement-based mixture, and the crushed stone particles are separated to obtain coarse and fine aggregates; S3, mixing the heat-activated slag-cement-based mixture and water glass to form a slurry; S4. Mix the pure paste with water, coarse and fine aggregates and external materials to form concrete.

[0131] The coarse and fine aggregates include coarse aggregate with a particle size of 10 mm and graded sand fine aggregate with a particle size of 2 mm.

[0132] The slag in step S1 is dried at a high temperature of 110°C for 24 hours, and the calcination temperature in step S2 is 750°C.

[0133] Calculated by mass ratio, the ratio of heat-activated slag-cement-based mixture: water glass: sand fine aggregate: coarse aggregate: water is 1:0.6:2.8:2.0:0.2.

[0134] When activated slag is mixed with cement, the water-solid ratio is controlled to be 38%, the alkali content is 10%; the particle size is 0.50mm, and the dry density of slag is 1.5g / cm 3。

[0135] The added materials include fly ash and ground granulated blast furnace slag. The fly ash particle size is 35μm and the specific surface area is 450m 2 / kg, the particle size of ground granulated blast furnace slag is 25μm and the specific surface area is 500m² / kg.

[0136] The fly ash is Class F fly ash, and the ground granulated blast furnace slag is S105 ground granulated blast furnace slag. Class F fly ash accounts for 2% of the total mass of the neat paste, water, and coarse and fine aggregates, and S105 ground granulated blast furnace slag accounts for 6% of the total mass of the neat paste, water, and coarse and fine aggregates.

[0137] The added materials also include carbon fiber, steel fiber, waste shell powder, rubber powder, glass fiber, retarder and water reducer. The carbon fiber accounts for 0.8% of the total mass of the neat paste, water and coarse and fine aggregates, the steel fiber accounts for 1% of the total mass of the neat paste, water and coarse and fine aggregates, the waste shell powder accounts for 0.5% of the total mass of the neat paste, water and coarse and fine aggregates, the rubber powder accounts for 1.5% of the total mass of the neat paste, water and coarse and fine aggregates, the glass fiber accounts for 1.0% of the total mass of the neat paste, water and coarse and fine aggregates, the retarder accounts for 0.1% of the total mass of the neat paste, water and coarse and fine aggregates, and the water reducer accounts for 0.3% of the total mass of the neat paste, water and coarse and fine aggregates.

[0138] The steel fiber is a fine steel fiber with a diameter of 0.2 mm.

[0139] The carbon fiber is a carbon fiber with a diameter of 5 μm.

[0140] The glass fibers were chopped glass fibers with a diameter of 10 mm.

[0141] The retarder is sodium gluconate.

[0142] The water reducer is a polycarboxylic acid water reducer whose main chain is a copolymer of methacrylic acid and methyl acrylate and whose side chain is a polyoxyethylene.

[0143] The ratio of heat-activated slag:cement:sodium hydroxide powder in the heat-activated slag-cement-based mixture is 1:1:0.05.

[0144] Comparative Example 1 The main difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, the slag powder in step S1 is directly mixed with cement to form a heat-activated slag-cement-based mixture. The remaining steps and component parameters of Comparative Example 1 are the same as those of Example 1.

[0145] Comparative Example 2 The main difference between Comparative Example 2 and Example 2 is that in Comparative Example 2, the heat-activated slag-cement-based mixture in step S2 is directly mixed with water glass coarse and fine aggregates and external additives to form concrete. The remaining steps and component parameters of Comparative Example 2 are the same as those of Example 2.

[0146] Comparative Example 3 The main difference between Comparative Example 3 and Example 1 is that the external additive is omitted in Comparative Example 3, and the amount of the external additive is supplemented to the heat-activated slag-cement-based mixture. The remaining steps and component parameters of Comparative Example 3 are the same as those of Example 1.

[0147] Comparative Example 4 The main difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, all the added materials are converted into Class F fly ash and S105 ground granulated blast furnace slag in proportion. The remaining steps and component parameters of Comparative Example 4 are the same as those of Example 1.

[0148] Comparative Example 5 The main difference between Comparative Example 5 and Example 1 is that in Comparative Example 5, the slag powder is directly calcined and then mixed with cement, and no sodium hydroxide is added to the slag powder during the calcination process. The remaining steps and component parameters of Comparative Example 5 are the same as those of Example 1.

[0149] The testing standard is the RCM method in GB / T50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" for chloride ion permeability test; GB / T50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete" for compressive strength and flexural strength test. GB / T50080 is used for slump test.

[0150] The test data are shown in Table 1 and Table 2: Table 1: Performance test results of Examples 1-5

[0151] Table 2: Performance test results of comparative examples 1-5

[0152] Specifically, as can be seen from Table 1, Examples 1-5 exhibit good mechanical properties, anti-permeability properties and processing properties. In Examples 1-5, components are prepared by mixing heat-activated slag and ordinary cement, and adding alkali-activated materials, which can effectively realize the application of slag-cement-based polymer concrete prefabricated steel columns. In conjunction with prefabricated beam-column nodes, the assembled construction of the composite structure can be realized, and the recycling of solid waste materials can be realized. Examples 1-5 greatly reduce the dependence on traditional cement by adding heat-activated slag to traditional cement, reduce carbon emissions from raw material production, and respond to the country's call for energy conservation and emission reduction; using activated slag to replace 50% of cement can achieve higher concrete strength, reduce total energy consumption by about 30%, and reduce carbon dioxide generation by about 40%. By adjusting the mix ratio, relying on strength and durability indicators, the application scenarios can be further expanded.

[0153] As can be seen from Table 2, the compressive strength and flexural strength of Comparative Example 1 are both worse than those of Example 1. Compared with Example 1, Comparative Example 1 directly mixes the slag powder in step S1 with cement to form a heat-activated slag-cement-based mixture. The slag powder is calcined, and the calcined slag can better react with components such as sodium silicate in water glass to form a gel network with good adhesion and strength. Therefore, the mechanical properties and anti-permeability properties of Comparative Example 1 are worse than those of Example 1.

[0154] Comparative Example 2 Compared with Example 2, in Comparative Example 2, the heat-activated slag-cement-based mixture in step S2 is directly stirred with water glass coarse and fine aggregates and additives to form concrete. Water glass can further improve the cohesiveness of the paste, and the combination of the paste and coarse and fine aggregates can make the internal structure of the concrete more compact. The water-to-solid ratio range of Example 2 helps to optimize the working performance of the paste, and the paste can maintain good fluidity and cohesiveness, which is convenient for construction operations. The mechanical properties, processing properties, and anti-penetration properties of Comparative Example 2 are worse than those of Example 2.

[0155] Comparative Example 3 Compared with Example 1, the additive is omitted in Comparative Example 3, and the amount of the additive is supplemented to the heat-activated slag-cement-based mixture. Among the additives, carbon fiber, steel fiber, waste shell powder, rubber powder, glass fiber, and water reducing agent can improve the mechanical properties, structural tightness, and processing performance of concrete. Therefore, the detection performance of Comparative Example 3 is worse than that of Example 1.

[0156] Compared with Example 1, Comparative Example 4 converts all the added materials into F-type fly ash and S105 ground granulated blast furnace slag in proportion. Among the added materials, carbon fiber, steel fiber, waste shell powder, rubber powder, glass fiber and water reducer can supplement the mechanical properties, structural tightness and processing performance of concrete that F-type fly ash and S105 ground granulated blast furnace slag cannot provide. Therefore, the detection performance of Comparative Example 4 is worse than that of Example 1.

[0157] Comparative Example 5 Compared with Example 1, in Comparative Example 5, the slag powder is directly calcined and then mixed with cement, and no sodium hydroxide is added to the slag powder during the calcination process. Sodium hydroxide, as an activator, can effectively stimulate the activity of the slag within this ratio range. It can destroy the original mineral structure in the slag, so that the components such as silicate and aluminate therein release active silicon ions and aluminum ions. These ions can participate in the subsequent gelling reaction, and together with cement and other components, form a stable gelling network structure, thereby improving the strength and durability of the concrete. A lower sodium hydroxide ratio can activate the activity of the slag while avoiding the alkali-aggregate reaction caused by excessive alkali content. The alkali-aggregate reaction can cause expansion, cracking and other problems inside the concrete, seriously affecting the durability of the concrete. At this ratio, the amount of alkali can be effectively controlled, and while exerting its stimulating effect, the long-term performance stability of the concrete is guaranteed. Therefore, the detection performance of Comparative Example 5 is worse than that of Example 1.

[0158] Example 6 The invention also comprises a prefabricated steel column made of concrete obtained by a method for preparing low-alkali heat-activated slag-cement-based mixed geopolymer concrete.

[0159] The configured heat-activated slag-cement-based concrete ratio is used for batch factory production. The factory realizes the reception of engineering slag, drying, screening and classification, high-temperature calcination to activate the activity of the mixture, and then excitation by alkaline activator to form heat-activated slag-cement-based polymer concrete. The factory high-temperature curing is used to realize the whole production process of engineering prefabricated components. The prefabricated components are prefabricated steel columns, which are connected with the beam-column node bolts through the steel column frame to form an overall structure. The cross-section of the prefabricated steel column is 900mm×1100mm.

[0160] Analysis of bearing capacity of prefabricated steel columns The load design requirements should be considered when designing the composite columns of cross-shaped steel and heat-activated slag-cement-based polymer concrete, and the load combination should be carried out according to the ultimate limit state of bearing capacity. Considering that the prefabricated steel column is mainly subjected to eccentric compression during the service stage, the most unfavorable effect combination should be taken for simulation stress analysis.

[0161] Load Analysis of Prefabricated Steel Column Components Figure 1-Figure 4As shown, prefabricated steel columns can meet the C50 strength requirements and realize the application and promotion of heat-activated slag-cement mixture concrete components.

[0162] The above is a preferred embodiment of the present invention. Relevant personnel in this technical field may make several improvements and modifications without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing low-alkali heat-activated slag-cement-based mixed geopolymer concrete, characterized in that: The following steps are involved: S1. Take soil from the project excavation as raw material slag, and dry the taken slag through drying equipment; S2, the slag in step S1 is screened and divided into slag powder and crushed stone particles, the slag powder is mixed with sodium hydroxide, activated by heat treatment and calcination, and then mixed with cement to form a heat-activated slag-cement-based mixture, and the crushed stone particles are separated to obtain coarse and fine aggregates; S3, mixing the heat-activated slag-cement-based mixture and water glass to form a slurry; S4. Mix the pure paste with water, coarse and fine aggregates and external materials to form concrete.

2. The method for preparing low-alkali heat-activated slag-cement-based mixed geopolymer concrete according to claim 1, characterized in that: Coarse and fine aggregates include coarse aggregate with a particle size of 5mm-25mm and graded sand fine aggregate with a particle size less than 5mm.

3. The method for preparing low-alkali heat-activated slag-cement-based mixed geopolymer concrete according to claim 1, characterized in that: The slag in step S1 is dried at a high temperature of 100-110°C for 24 hours, and the calcination temperature in step S2 is 700-750°C.

4. The method for preparing low-alkali heat-activated slag-cement-based mixed geopolymer concrete according to claim 2, characterized in that: Calculated by mass ratio, the ratio of heat-activated slag-cement-based mixture: water glass: sand fine aggregate: coarse aggregate: water is 1:0.5-0.6:2.4-2.8:1.5-2.0:0.1-0.

2.

5. The method for preparing low-alkali heat-activated slag-cement-based mixed geopolymer concrete according to claim 1, characterized in that: When activated slag is mixed with cement, the water-solid ratio is controlled to be 34%-38%, the alkali content is 8%-10%; the particle size is less than 1.00mm, and the dry density of slag is 1.4-1.5g / cm 3 .

6. The method for preparing low-alkali heat-activated slag-cement-based mixed geopolymer concrete according to claim 1, characterized in that: The added materials include fly ash and ground granulated blast furnace slag. The particle size of fly ash is less than 45μm and the specific surface area is 400m² / kg-450m 2 / kg, the particle size of ground granulated blast furnace slag is less than 45μm, and the specific surface area is 500m² / kg-520m² / kg.

7. The method for preparing low-alkali heat-activated slag-cement-based mixed geopolymer concrete according to claim 6, characterized in that: The fly ash is Class F fly ash, and the ground granulated blast furnace slag is S105 ground granulated blast furnace slag. Class F fly ash accounts for 1%-2% of the total mass of the neat paste, water, and coarse and fine aggregates, and S105 ground granulated blast furnace slag accounts for 4%-6% of the total mass of the neat paste, water, and coarse and fine aggregates.

8. The method for preparing low-alkali heat-activated slag-cement-based mixed geopolymer concrete according to claim 1, characterized in that: The added materials also include at least three of carbon fiber, steel fiber, waste shell powder, rubber powder, glass fiber, retarder and water reducer.

9. The method for preparing the low-alkali heat-activated slag-cement-based mixed geopolymer concrete according to claim 1, characterized in that: The ratio of heat-activated slag: cement: sodium hydroxide powder in the heat-activated slag-cement-based mixture is 1:1:0.04-0.

05.

10. Prefabricated steel column, characterized in that: The concrete is made by the method for preparing low-alkali heat-activated slag-cement-based mixed geopolymer concrete described in any one of claims 1 to 9.